2018
DOI: 10.1016/j.ijrobp.2018.07.2010
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl Sulfoxide Prevents Radiation-Induced Oral Mucositis Through Facilitating DNA Double-Strand Break Repair in Epithelial Stem Cells

Abstract: DMSO prevents the loss of proliferative lingual epithelial stem and progenitor cells upon irradiation by facilitating of DNA DSBs repair, thereby protecting from radiation-induced mucositis without tumor protection. Given its high efficacy and low toxicity, DMSO could be a potential treatment option to prevent radiation-induced oral mucositis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Recently, several studies also indicate that DMSO acts to facilitate the repair of DNA damage [ 26 , 49 , 59 , 67 ]. Radioprotection due to the presence of DMSO is manly from the facilitation of DNA damage repair rather than through the suppression of indirect actions [ 26 , 49 ]. Bajinskis et al (2013) reported that DMSO affects primarily on all DNA repair pathways [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, several studies also indicate that DMSO acts to facilitate the repair of DNA damage [ 26 , 49 , 59 , 67 ]. Radioprotection due to the presence of DMSO is manly from the facilitation of DNA damage repair rather than through the suppression of indirect actions [ 26 , 49 ]. Bajinskis et al (2013) reported that DMSO affects primarily on all DNA repair pathways [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bajinskis et al (2013) reported that DMSO affects primarily on all DNA repair pathways [ 59 ]. Yang et al suggested that DMSO may facilitate the DSB repair pathways only [ 26 ]. Our study showed that the mutation probabilities of BER and NER pathways for 60 Co γ-rays, proton ions and high-LET helium ions were all respectively reduced by 35–39%, 43–48% and 16–31% in the presence of 2 M DMSO, indicating that DMSO might also alleviate the BER and NER repair pathways.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations